A socio-technical approach to the evaluation of social credit applications - Ferreira, F.; Esperança, J.; Xavier, M.; Costa, R.; Pérez-Gladish, B. (Journal of the Operational Research Society, 2019)
Social credit is a type of micro-credit aiming at fighting poverty and social inequality. Although interest in this type of credit has increased significantly over time, namely after Muhammad Yunus was awarded the 2006 Nobel Peace Prize, there are few studies that address the assessment of social credit applications. This is an issue to be taken seriously primarily because the objectives of social credit differ from those of other types of credit, meaning that social credit applications should not be evaluated using the same credit-scoring systems. Assuming the baseline principles of the multiple criteria decision analysis (MCDA) approach, this study combines cognitive mapping and measuring attractiveness by a categorical-based evaluation technique (MACBETH) to develop an evaluation system for social credit applications. The results show that the social-technical approach followed in this study provides value for the evaluation processes of this type of credit application as a result of the privileged contact established with a panel of credit analysts. The advantages, limitations and managerial implications of our study are also discussed.